(untitled) (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2021)
Raquel Forner (Buenos Aires 1902-1988) was one of the most relevant female artists in the history of 20th century Argentine art. This work aims to highlight her work, by investigating her pictorial production during two stages of her career. The first stage comprises the 1930s / 1940s, when she focused on the Spanish Civil War and World War II, placing women at the center of her paintings and using expressionist and metaphysical aesthetics. During the other stage, from the late 1950s until her death in 1988, she focused on the conquest of space and the rise of the mass media and its impact on society, using informalist and neo-figurative languages.